2016
DOI: 10.5935/0034-7280.20160089
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and incidence of diabetic retinopathy

Abstract: Objective:The present study aims to evaluate the incidence, and risk factors of diabetic retinopathy( disease duration and the presence of hypertension).Study carried out at Instituto

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
2
1
0
1
Order By: Relevance
“…In our study we found that patients with poor glycemic control (HbA1c >7%) had more severe diabetic retinopathy than patients with good glycemic control (HbA1c <7%). This coincides with the findings of CURES Eye Study (2008), 12 DCCT (The Diabetes Control and Complications Trial) (1993), 14 UKPDS (United Kingdom Prospective Diabetes Study) (1998), 15 and Ramachandran Rajalakshmi et al (2016). 16 On comparing patients with hypertension or without hypertension, we found that there was a statistically significant difference between the severities of diabetic retinopathy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study we found that patients with poor glycemic control (HbA1c >7%) had more severe diabetic retinopathy than patients with good glycemic control (HbA1c <7%). This coincides with the findings of CURES Eye Study (2008), 12 DCCT (The Diabetes Control and Complications Trial) (1993), 14 UKPDS (United Kingdom Prospective Diabetes Study) (1998), 15 and Ramachandran Rajalakshmi et al (2016). 16 On comparing patients with hypertension or without hypertension, we found that there was a statistically significant difference between the severities of diabetic retinopathy.…”
Section: Discussionsupporting
confidence: 86%
“…Duration of DM was a significant risk factor in our study. CURES (Chennai Urban Rural Epidemiology Eye Study) (2008) 12 and Irini P Chatziralli et al (2010) 13 found similar results in their study. In our study we found that patients with poor glycemic control (HbA1c >7%) had more severe diabetic retinopathy than patients with good glycemic control (HbA1c <7%).…”
Section: Discussionsupporting
confidence: 66%
“…Younger age [9,12], together with longer diabetes duration, triglyceride and low density lipoprotein and glycosylated haemoglobin have been associated with diabetic retinopathy [13,14]. Other risk factors are type 1 diabetes for over a decade [15], nephropathy [16], sedentary lifestyle [17], systemic arterial hypertension [18], obesity, pregnancy, cataract surgery, genetics and puberty [19]. This makes timely and regular screening for diabetic retinopathy very important in the management of diabetic patients.…”
Section: A Demographic Characteristicsmentioning
confidence: 99%
“…A magnitude desse desafio é acentuada pela complexidade multifatorial da doença, demandando uma intervenção abrangente que transcenda os limites da prática clínica convencional. No cenário brasileiro, caracterizado por disparidades socioeconômicas e desafios estruturais no sistema de saúde pública, a implementação de estratégias integradas surge como uma resposta imperativa para otimizar a eficiência dos cuidados oftalmológicos destinados aos pacientes diabéticos (Mendanha et al, 2016).…”
Section: Introductionunclassified